Pyau constructed by the descendants of Nawab Ayaz - Mumbai Archive Project Team (Jio Institute, 2024)
As a gesture of goodwill and public service, the descendants of Nawab Ayaz supported the construction of a sizable tank on the site of which a pyau (drinking waterspout) was placed in 1916. Horses and bullocks that pulled carts carrying cargo to the warehouses and dockyards had their own section of the tank. Subsequently, the tank was filled and transformed into a playground. It also has a subterranean water tank.